2009
DOI: 10.1523/jneurosci.2119-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Bed Nucleus of the Stria Terminalis Mediates Inter-individual Variations in Anxiety and Fear

Abstract: While learning to fear stimuli that predict danger promotes survival, the inability to inhibit fear to inappropriate cues leads to a pernicious cycle of avoidance behaviors. Previous studies have revealed large inter-individual variations in fear responding with clinically anxious humans exhibiting a tendency to generalize learned fear to safe stimuli or situations. To shed light on the origin of these inter-individual variations, we subjected rats to a differential auditory fear conditioning paradigm in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
197
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(217 citation statements)
references
References 43 publications
17
197
1
2
Order By: Relevance
“…In fact, several studies have dissected the involvement of different brain regions in the processing of contextual and cued fear memory (Orsini and Maren, 2012), albeit the expression of both forms of contextual fear mostly depend on amygdala circuits (Goosens and Maren, 2001). This is heralded by the differential impact on cued and contextual fear memory upon manipulation of different molecular targets (eg, Sui et al, 2006;Burghart and Bauer, 2013) or lesions/inactivation (eg, Duvarci et al, 2009;Baldi et al, 2013) in different brain regions. This apparent different involvement of A 2A Rs in the amygdala and in other brain regions in the acquisition and expression of contextual fear, which still remains to be detailed, does not undermine the key impact of A 2A R blockade in long-term contextual fear, a conclusion of particular importance in view of the prominent role of contextualization in behavioral flexibility and psychopathology (reviewed in Maren et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have dissected the involvement of different brain regions in the processing of contextual and cued fear memory (Orsini and Maren, 2012), albeit the expression of both forms of contextual fear mostly depend on amygdala circuits (Goosens and Maren, 2001). This is heralded by the differential impact on cued and contextual fear memory upon manipulation of different molecular targets (eg, Sui et al, 2006;Burghart and Bauer, 2013) or lesions/inactivation (eg, Duvarci et al, 2009;Baldi et al, 2013) in different brain regions. This apparent different involvement of A 2A Rs in the amygdala and in other brain regions in the acquisition and expression of contextual fear, which still remains to be detailed, does not undermine the key impact of A 2A R blockade in long-term contextual fear, a conclusion of particular importance in view of the prominent role of contextualization in behavioral flexibility and psychopathology (reviewed in Maren et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are a number of rodent models in which a specific rat or mouse strain (Cohen et al, 2008), sub-population (Duvarci et al, 2009), or selectively bred line (Muigg et al, 2008) exhibits features consistent with inherent susceptibility to excessive fear after an experimental trauma such as Pavlovian fear conditioning. Along these lines, we recently identified an inbred mouse strain, 129S1/SvImJ (S1), which displays a profound deficit in cued fear extinction, coupled with functional abnormalities in corticoamygdala circuitry mediating extinction (Camp et al, 2009;Hefner et al, 2008;Whittle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…electrical shock) through associative Pavlovian conditioning can subsequently shift the tuning curves of neurons in sensory cortices towards the characteristic sensory features of the conditioned stimulus and/or increase the number of neurons representing that stimulus (Gdalyahu et al, 2012;Resnik et al, 2011;Weinberger, 2004Weinberger, , 2007. Such remodeling of sensory representations may critically depend on modulatory signals from the amygdala (Armony et al, 1997;Chavez et al, 2009;Duvarci et al, 2009;Shaban et al, 2006). Likewise, in humans, Li et al (2008) showed that initially indistinguishable odors (mirror-image molecules) can be transformed into discriminable percepts after aversive conditioning, associated with distinctive activations in the olfactory cortex as demonstrated by functional Magnetic Resonance Imaging (fMRI).…”
Section: Introductionmentioning
confidence: 99%